Does cognitive behavioural therapy have a role in improving problem solving and coping in adolescents with suicidal ideation?. (December 2014) - Hetrick, Sarah; Yuen, Hok Pan; Cox, Georgina; Bendall, Sarah; Yung, Alison; Pirkis, Jane; Robinson, Jo
Abstract: Problem-solving and coping skills deficits have been shown in adolescents who experience suicide-related behaviours, including suicidal ideation. Little evidence exists about effective interventions for this population. We undertook a pilot study of an Internet-based CBT programme that included problem-solving skills training to investigate its impact on skills deficits. The study employed a pre-test/post-test design. Outcomes of interest were negative problem orientation, emotion- and task-focused coping, and adolescents' perception of helpfulness of the intervention. Participants, recruited via the school wellbeing team, were assessed at baseline, at weekly intervention sessions and immediately post-intervention. Twenty-one adolescents completed the intervention. Over the course of the intervention, negative problem-solving orientation improved and students relied less on emotion-focused coping strategies. Because there was no control group, we cannot be certain that the changes seen between baseline and post-intervention can be attributed to the intervention. Adolescents rated the problem-solving and cognitive restructuring modules as particularly helpful. Interventions that include enhancement of problem-solving skills, as well as cognitive restructuring to address adolescents' appraisal of problems and their ability to solve them appear promising for adolescents with suicidal ideation. Further investigation is warranted.